Initial development and validation of the career readiness cognitive information processing module among university students - Mahmud, Mohd Izwan; Noah, Sidek Mohd; Ahmad, Jamaludin; Wan Jaafar, Wan Marzuki; Amat, Salleh; Abu Bakar, Abu Yazid (Primrose Hall Publishing Group, 2019)
The career development of university students is a transition process from education to career that needs them to be ready to plan, explore, make choices and make career decisions appropriate with one’s interest, talent and ability. Career readiness can be enhanced through involvement of the students in suitable career development programs. Thus, the Career Readiness Cognitive Information Processing Module (CRCIPM) was developed as an intervention aimed to increase the students’ career readiness. This module consists of three sub-modules, which are knowledge sub-module, decision making sub-module and information processing sub-module; and thirteen activities that were developed based on Cognitive Information Processing (CIP) theory. The research aim to analysis the content validity and reliability of CRCIPM. This research used the descriptive research design, where the expert consensus percentage value and module’s content validity coefficient as well as reliability coefficient were obtained using the Alpha Cronbach coefficient internal validity. Meanwhile, a total of 28 students were used as the samples of the pilot test in order to obtain the reliability coefficient value of the modules. The questionnaire consisted of four items which were: the module content is suitable for the targeted population, the module content can be implemented successfully, the module content can increase career readiness and the module content can modify the career thoughts. The research findings showed that the value of content validity coefficient was .955 and based on the sub-modules and activities was .934. The findings of the pilot test showed that the module’s Alpha Cronbach value of reliability was .945. This proves that the CRCIPM has high content validity and reliability, and therefore is suitable to be implemented on the university students that have low or moderate level of career readiness. Further research needs to be done in order to test the effectiveness of the module on the population. This research contributes to the development of the module in career counselling for higher education students.